Stress and academic performance among accounting graduate students in Brazil - Rezende, Marise Santana de; Miranda, Gilberto José; Pereira, Janser Moura; Cornacchione Júnior, Edgard Bruno (Education Policy Analysis Archives, 2017)
Postgraduate admission is an important transition in the student’s life, since this period can be understood as a process that involves a series of changes, pressures and changes that require the individual to adapt to the academic context. With this perspective, this research had a general objective: to identify and analyze the relationship between stress and academic performance realized by undergraduate students stricto sensu in Accounting in Brazil. For the accomplishment of this research, a sample of 309 students (24.08% of the population) who studied postgraduate in Accounting Sciences were investigated. Through a two-step multiple regression analysis, this study found that the research line, the condition of a student with scholarship and the age of the program, as well as the concerns and difficulties inherent in the process, significantly influence the student's level of stress. It also showed that the student's previous academic performance and stress level are significant in explaining academic performance. These results highlight the importance of monitoring the above-identified items of stress for the maintenance of student’s performance, as well as avoiding other problems due to the drop in performance, such as avoidance and other major damages.